2016
DOI: 10.1080/15384101.2016.1196303
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of KSHV-induced angiopoietin-2 inhibits angiogenesis, infiltration of inflammatory cells, and tumor growth

Abstract: Kaposi's sarcoma (KS) is a highly angiogenic and inflammatory neoplasia. The angiogenic and inflammatory cytokine angiopoietin-2 (Ang-2) is strongly expressed in KS due to Kaposi's sarcoma-associated herpesvirus (KSHV) infection. In the present study, we determined how Ang-2 contributes to development of KS by using telomerase-immortalized human umbilical vein endothelial cells (TIVE) as a model, which become malignantly transformed and express increased levels of Ang-2 following KSHV infection. Ang-2 released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…We previously reported that KSHV infection of endothelial cells induces the angiogenic and inflammatory cytokine Ang-2 to promote migration and recruitment of monocytes into tumors. 12 In the present study, we found that KSHV infection of endothelial cells strongly induces expression and release of IL-6, IL-10, and IL-13 that individually and collectively promote differentiation and polarization of monocytes into TAMs. The KSHV-induced TAMs express well-known TAM-specific markers such as CD-163 and LGMN, promote angiogenesis, and significantly enhance tumor growth in nude mice.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We previously reported that KSHV infection of endothelial cells induces the angiogenic and inflammatory cytokine Ang-2 to promote migration and recruitment of monocytes into tumors. 12 In the present study, we found that KSHV infection of endothelial cells strongly induces expression and release of IL-6, IL-10, and IL-13 that individually and collectively promote differentiation and polarization of monocytes into TAMs. The KSHV-induced TAMs express well-known TAM-specific markers such as CD-163 and LGMN, promote angiogenesis, and significantly enhance tumor growth in nude mice.…”
Section: Discussionsupporting
confidence: 55%
“…We previously showed that KSHV infection of endothelial cells induces Ang-2 to promote migration and recruitment of monocytes into KS tumors. 12 We suspected that KSHV infection of endothelial cells induce additional cytokines that drive the recruited monocytes to differentiate and polarize into TAMs. To test this hypothesis, we infected human umbilical vein endothelial cells (HUVECs) with mock or purified recombinant KSHV, BAC16, 38 for various time points, followed by measurement of expression of TAM-promoting cytokines such as IL-4, IL-6, IL-10, IL-13, and M-CSF.…”
Section: Kshv Infection Of Endothelial Cells Induces Tamspromoting Cymentioning
confidence: 99%
See 1 more Smart Citation
“…Adding Ang-2 neutralization antibody into the Matrigel effectively blocked the angiogenic effect of KSHV-induced Ang-2. This data is concordant with a recent study using a KSHV-induced endothelial cell tumor model that strongly expressed Ang-2 [94,169]. When equal numbers of the KSHV-induced tumor cells were used in a Matrigel-based angiogenesis assay in nude mice, inclusion of AMG-138 or L1-10, two peptide-based Ang-2 inhibitors [81], substantially reduced the numbers of blood vessels.…”
Section: Ang-2 Promotes Angiogenesis Inflammation and Ks Tumor Growthsupporting
confidence: 90%
“…One study demonstrated that administration of Ang-2, but not Ang-1, induced edema in the mouse paw in a dose-dependent manner [90], which was blocked by co-administration of soluble Tie-2. Both Ang-1 and Ang-2 demonstrated the abilities to attract migration of inflammatory cells such as neutrophils and monocytes [90][91][92][93][94]. Chemotaxis seems to be a driving force for Ang-1/Ang-2 mediated migration of inflammatory cells [92].…”
Section: Roles Of Angiopoietins In Tumor Inflammation and Microenviromentioning
confidence: 99%